PENGARUH YOGA TERHADAP TINGKAT KECEMASAN IBU NIFAS DI PUSKESMAS PADANG KABUPATEN LUMAJANG - Kartikasari, Tititan Nur Ari Dwi; Keswara, Nila Widya; Maulina, Rifzul (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Postpartum mothers experience various significant physical and emotional changes after giving birth, which can trigger anxiety. Anxiety in postpartum mothers can have a negative influence on the baby's growth and development, the mental health of the individual mother, and the mother's role as a wife. Efforts to handle or minimize postpartum anxiety can be done in several ways, one of which is by doing yoga for postpartum mothers. The purpose of this study was to analyze the effect of yoga on the anxiety level of postpartum mothers in Padang Health Center, Lumajang. The research method used is one group pretest posttest design. Sampling using purposive sampling, the number of samples is 30 respondents. The research instrument used a questionnaire. The results showed that the results of statistical tests using the Wilcoxon test obtained a p value of 0.001 (p < 0.05), so it can be concluded that there is a significant influence between the anxiety level of postpartum mothers before and after warm breast compresses, with a 3-fold reduction in anxiety levels. Anxiety decreased by 30 respondents. Postpartum mothers are expected to be able to follow or practice yoga movements regularly, namely 1-2 times a week as an alternative to achieve a feeling of comfort, relaxation and help reduce complaints during the postpartum period. Apart from that, it is hoped that midwives can provide yoga intervention as an effort to help reduce the anxiety level of postpartum mothers.